Modelling Ocean Connectivity - Margherita Paola Poto (Cappelen Damm Akademisk NOASP, 2021)
Regulatory coherence is crucial to effectively respond to the growing pressures that our oceans are facing. Applying the interpretative lens of ocean connectivity to ocean governance can help address the challenges from a material, epistemic, and geopolitical viewpoint. This special issue intends to uncover various understandings of ocean connectivity taking into account the complex biocultural interactions happening in the marine environment. The research aim is divided into two objectives: (1) to explore the various conceptualizations of ocean connectivity; and (2) to provide a critical analysis on how the law (of the sea) considers or disregards ocean connectivity. Our research methodology combines a literature review and a mapping technique that examines the models of connectivity. The mapping technique has been developed by adopting the ‘one-pager approach’, where the authors have been asked to answer two research questions, aligned with our research objectives. We structured the work into an introductory section and three main articles. The understanding of ocean connectivity is key to developing international marine policy and suggesting legal tools for the protection of the marine environment. Moving from this angle towards an understanding of connectivity which includes bio-centric elements, Indigenous cosmo-visions, and anthropocentric connectivity, we identified three models of connectivity and explored their suitability to address the systemic challenges.